'Secure in the Two-Dimensional World': The Filmbühne and Jewish Audiences in the Third Reich, 1938–1941. Issue 3 (2nd September 2017) - Hansen Rauch, Leah
ABSTRACT: This article presents the first in-depth study of the impact the Filmbühne (film stage) had in the lives of German Jews living under the systematic oppression of the Nazi regime. The Filmbühne was an extension of the Jüdischer Kulturbund, a Jewish organization which offered cultural activities exclusively for Jews in the Third Reich between 1933 and 1941. The Filmbühne opened in December 1938 and provided Jews in Berlin an opportunity to view films, an activity which had been forbidden to them in the previous month. This article presents a first thorough reconstruction of the Filmbühne itself, including who attended the film screenings, what was shown, the cinema's function within the larger Kulturbund organization and why the Nazi authorities allowed it to exist. It then considers the different ways the Filmbühne affected German Jews' daily lives as seen through letters and diaries. The final section shows how film reviews in the Jüdisches Nachrichtenblatt, the only surviving Jewish newspaper at the time, enabled members of the Jewish community to circumvent Nazi censorship concerning Kristallnacht. This study discusses the variety of ways that the Filmbühne affected the lives of German Jews, most notably by providing audiences a way to cope with reality, connecting the Jewish community with the larger German culture, from which its members were completely segregated in other areas of their lives, and serving as a valuable communication tool which sent messages of validation and encouragement to the Jewish community. Focusing on this largely overlooked organization offers a new perspective on Jewish life in Nazi Germany during the period of time after Kristallnacht and before the deportations.